Sodium adsorption by reusable zeolite adsorbents: integrated adsorption cycles for salinised groundwater treatment. Issue 20 (6th September 2021) - Siemens, Ashley M.; Dynes, James J.; Chang, Wonjae
ABSTRACT: Using Canadian (CMZ), Bear River (BRZ), and St. Cloud (SCZ) zeolites, this study investigates the application of natural and pre-treated zeolites for Na + removal from salinised groundwater. Natural BRZ achieved better Na + removal for initial concentrations of 250–10, 000 mg Na + /L and had the highest maximum adsorption capacity (14.3 ± 0.4 mg/g) compared to natural CMZ (5.8 ± 0.5 mg/g) and SCZ (5.6 ± 0.7 mg/g). Natural BRZ exhibited a higher cation exchange capacity (CEC), mineralogical purity, and natural abundance of exchangeable calcium. The natural abundance of Na + on CMZ and SCZ may have reduced Na + adsorption. H-form BRZ and H-form CMZ were also prepared through conventional acidic pre-treatment. Acid treatment improved zeolite properties for adsorption (surface area and CEC). Synchrotron-based X-ray scanning transmission microscopy (STXM) indicated that Na + adsorption sites in the H-form zeolites were associated with the mineral framework. However, sorption effluents were highly acidic (pH ∼2) and Al 3+ leached significantly due to the dealumination induced by acid treatment. Alternatively, hard water softening was cyclically integrated with sodium adsorption as a zeolite treatment to generate Ca/Mg-form CMZ. This integration suggested the feasibility of combining CMZ cycles for water softening and sodium reduction for an extended CMZ lifecycle. Natural CMZ was first used to treat hard water, which enriched the CMZ with Ca 2+ and Mg 2+ and increased its subsequent Na + removal rate by over 77%, without producing acidic effluents. The Canadian zeolite adsorbed more sodium when water softening was integrated with sodium removal, which is a repeatable dual-treatment. GRAPHICAL ABSTRACT: UF0001